The Pharmacology and Therapeutic Implications of Capsaicin (International Journal of Food and Nutritional Sciences, 2022)
Capsaicin, a naturally occurring chemical found in chilli peppers, is what gives them their characteristically fiery flavour. An odourless fat-soluble chemical, it is quickly absorbed by the skin. Capsaicin's analgesic effects can be attributed to its ability to block the Transient Receptor Potential action channel (subfamily V), type 1 (TRPV1) in small fibre nociceptor neurons. Specifically, it binds to the vanilloid receptor TRPV1, which mediates the combined effects of chemical and mechanical pain inputs at the molecular level.Using capsaicin topically can help with the discomfort of both diabetic neuropathy and chronic musculoskeletal pain. In patients with bladder hyperactivity, it is used to enlarge the bladder and lessen the frequency of incontinence. When applied to acupuncture points, capsaicin prevents post-operative nausea and vomiting. It has potential as a therapy for pruritis related to renal failure and as a gastric barrier against the side effects of non-steroidal anti-inflammatory drugs. In the future, capsaicin analogues and TRPV1 antagonists may deliver more effective and better tolerated medicinal treatments